2008
DOI: 10.1086/586709
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Major Histocompatibility Complex Class I Chain–Related Molecule A, NKG2D, and Transforming Growth Factor–β in the Liver of Humans with Alveolar Echinococcosis: New Actors in the Tolerance to Parasites?

Abstract: Sustained expression of MICA/B molecules and TGF-beta might lead to modulation of NKG2D with subsequent inhibition of NKG2D-dependent cytotoxicity. Abnormalities of this signaling system could contribute to parasitic evasion of the host's immunity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
77
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(82 citation statements)
references
References 48 publications
4
77
0
1
Order By: Relevance
“…A hallmark of chronic Echinococcus infection is the presence of high levels of IL-10 (Zhang et al, 2008a;Vuitton, 2003), a cytokine typically associated with immunoregulation of effector responses (Moore et al, 2001). The role of IL-10 in chronic infection largely remains unclear, although one report showed that IL-10 may impair the Th1 protective response and allow the parasite to survive in hydatid patients (Moore et al, 2001).…”
Section: T Cell Responsesmentioning
confidence: 99%
See 1 more Smart Citation
“…A hallmark of chronic Echinococcus infection is the presence of high levels of IL-10 (Zhang et al, 2008a;Vuitton, 2003), a cytokine typically associated with immunoregulation of effector responses (Moore et al, 2001). The role of IL-10 in chronic infection largely remains unclear, although one report showed that IL-10 may impair the Th1 protective response and allow the parasite to survive in hydatid patients (Moore et al, 2001).…”
Section: T Cell Responsesmentioning
confidence: 99%
“…The role of IL-10 in chronic infection largely remains unclear, although one report showed that IL-10 may impair the Th1 protective response and allow the parasite to survive in hydatid patients (Moore et al, 2001). By inducing the host to produce high levels of IL-10, E. multilocularis appears able to modulate the immune response so that the T cells infiltrating the periparasitic granuloma cannot participate in the effector phase of the cellular immune response (Zhang et al, 2008a;Vuitton, 2003). The interaction of the Echinococcus organisms with their mammalian hosts may provide a highly suitable model to address some of the fundamental questions remaining such as the molecular basis underpinning the different effects of IL-10 on different cell types; the mechanisms of regulation of IL-10 production; the inhibitory role of IL-10 on monocyte/macrophage and CD4 T cell function; its involvement in stimulating the development of B cells and CD8 T cells; and its role in the differentiation and function of T regulatory cells.…”
Section: T Cell Responsesmentioning
confidence: 99%
“…There have been few studies that have investigated NK cells in Echinococcus infection, although these cells are known to be instrumental in innate immune responses against intracellular pathogens including viruses, bacteria, and protozoa (17). Patients with active CE cysts were shown to have proportionally more NK cells (CD56 ϩ CD8 Ϫ ) in their PBMC than controls (18), but no functional studies or in situ analysis of the cells at the periphery of the cysts were undertaken, so their role in the outcome of hydatid disease was not determined.…”
Section: Figurementioning
confidence: 99%
“…In contrast, patients with AE infection had a lower level of PBMC NK activity than healthy controls and subjects with nonparasitic biliary disease; this could be due to a lower percentage of NK cells circulating in the blood of the AE patients or to the presence of serum inhibitory factors such as immune complexes or Abs (19). It has been hypothesized that in AE the MHC class I chain-related molecules A and B (MICA/B), induced by E. multilocularis, skew the NKG2D activation pathway on NK and CD8 T cells, inhibiting NKG2D-dependent cytotoxicity and thereby contributing to the longevity of the parasite (17).…”
Section: Figurementioning
confidence: 99%
“…IL-10 is spontaneously secreted by PBMCs in patients with progressing alveolar echinococcosis lesions [144], but the highest concentration of IL-10 might be found in the periparasitic granuloma, where it is produced by T cells closest to the parasitic vesicles [145]. Similarly, TGFβ-secreting cells are present in the granuloma, although their identity is presently not clear [146].…”
Section: Echinococcosismentioning
confidence: 99%